Validity and Reliability of Roland-Morris Disability Questionnaire: Cross-Cultural Adaptation Study for Low Back Pain Disability - Regina, Ni Kadek Pramesti; Negara, Anak Agung Gede Angga Puspa; Kinandana, Gede Parta; Sugiritama, I Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/mifi.2024.v12.i03.p17, 2024)
Introduction: Around 60-80% of individuals experience low back pain in their lifetime, often leading to disability. The Roland-Morris Disability Questionnaire (RMDQ) is a tool used to assess disability caused by low back pain, measuring its impact on daily activities. To ensure its effectiveness, it is crucial to test the questionnaire's validity and reliability in different cultural contexts. Methods: This study employed a descriptive survey method and a cross-sectional design with a purposive sampling technique, involving 124 subjects. Content validity was assessed through expert evaluation using the Content Validity Index (CVI), while construct validity was measured using Pearson Product-Moment Correlation. Reliability was evaluated through Cronbach’s Alpha to assess internal consistency. Results: The analysis revealed weak to moderate construct validity values (0.361–0.402) and excellent content validity index scores (S-CVI/Ave=1). Reliability analysis demonstrated good reliability with a Cronbach’s Alpha value of 0.725. Conclusion: The Indonesian version of the RMDQ questionnaire is valid and reliable for evaluating low back pain disability. It is suitable for use in clinical practice, enabling Indonesian patients to comprehend the questionnaire without losing the essence of the original version. Further research is needed to explore the onset and causes of low back pain disability in more depth.   Keywords: cross-cultural adaptation, validity, reliability, Roland-Morris Disability Questionnaire, Indonesia